Variability of Ozone Deposition Velocity Over a Mixed Suburban Temperate Forest - Neirynck, Johan; Verstraeten, Arne (Frontiers in Environmental Science, 2018)
A 10-year long dataset of half-hourly ozone (O3) fluxes was used to study the variability in deposition velocity (υd) over a mixed temperate suburban forest. Average (median) υd amounted to 0.70 (0.46) cm s-1, with day- and night-time average (median) of 0.98 (0.73) cm s-1 and 0.46 (0.30) cm s-1, respectively. It was found that the precipitation form had a marked impact on υd and the deposition efficiency (υd/υdmax), with highest values measured when the canopy was dew-wetted or covered with snow. The analysis further evidenced that traffic volume led to increased deposition due to the presence of chemical reactions between O3 and nitric oxide (NO) above the canopy surface. During the working week, daytime values of υd, υd/υdmax and the O3 fluxes (F) were found to be significantly higher than the weekend values, especially during the winter half-year. In a next step, half hourly deposition data were aggregated into day- and night-time monthly values, for a correlative study with measured environmental variables. Monthly average night-time/daytime υd and υd/υdmax were positively correlated with the relative humidity at the canopy surface (RH(z0’)) and negatively correlated with the water levels below the ground surface. During the daytime, monthly υd and υd/υdmax were additionally increased during the working-week when traffic volume was high. There existed, however, substantially different weather conditions, in which unaccounted covariates with a totally different meteorological signature controlled the υd and F. It was speculated that, among other, biogenic volatile compounds (BVOCs) could have contributed to O3 quenching in some (spring) months with severe drought stress.